Pengaruh Konsentrasi Nikel dalam Klorofil pada Sifat Optik dan Konduktivitas Dye untuk Aplikasi Dye-Sensitized Solar Cell (DSSC) - Dinasti Dwi Pratiwi; K Kusumandari; Fahru Nurosyid (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2018)
This study aims to investigate the effect of nickel doping into chlorophyll dye on the optical properties and conductivity for DSSC application. The nickel doping is focused the effect of nickel concentration into chlorophyll dye as photosensitizer. Analysis of optical properties (absorbance) of dye solutions and TiO2 used the UV-Visible spectrophotometer. The conductivity of dye solutions were calculated using I-V meter. The characterization results of absorbance and conductivity of dye solutions were direcly proportional to increasing the Ni concentration. The FTIR characterization resulted the optimum absorption at a concentration of 0,1 M with the frequency peak of (Ni-Cl) at 679 cm-1. The absorbance of TiO2/dye also showed that the optimum doping concentration of 0,1 M.